Analysis of Brand Reputation and Brand Trust in Increasing Customer Loyalty of Local Cosmetic Brand (Survey of Emina Cosmetics Users in Sukabumi City) - Siti Nurlela Sari; Asep M. Ramdan; Faizal Mulia Z (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The purpose of this research is to measure how much influence brand reputation and brand trust have in increasing customer loyalty of local cosmetic brand Emina Cosmetics in Sukabumi City. The method used in this research is descriptive quantitative method and associative method with a quantitative approach. The sampling technique in this study used a non-probability sampling technique using purposive sampling involving 397 female respondents using Emina Cosmetics in Sukabumi City. The data analysis technique used is multiple linear regression analysis which includes multiple correlation coefficient test, coefficient of determination test, simultaneous test (F test) and partial test (T test). Research result by using the F. test shows that the calculated F valueof 256.896 > F table 3.01 with sig level. 0.00 0 < 0.05 which means that Brand Reputation (X1) and Brand Trust (X2) simultaneously have a positive and significant effect on Customer Loyalty (Y). Furthermore, using the T-test shows that each t - value Brand Reputation (X1) and Brand Trust (X2) equal to 10.878, 11.330 > t table 1.97 with sig level. 0.00 0 < 0.05 which means that Brand Reputation (X1) and Brand Trust (X2) partially have a positive and significant effect on Customer Loyalty (Y).